Teste e padronização de alvos recombinantes de proteínas para o diagnóstico da doença de Chagas - Ana Carolina Paes Martins Lanna (2015)
Chagas disease (CD), also known as American trypanosomiasis, is caused by the unicellular hemoflagellate parasite Trypanosoma cruzi. CD is an endemic disease in Latin America and emerging infectious disease in US and Europe. The acute phase of the disease lasts around 10 to 90 days after infection and is characterized by high parasitic load, which allows the diagnosis to be made by direct examination. At the chronic phase, that chagasic patient has a low parasitaemia and high titers of IgG against parasite antigens, hence, the diagnosis of Chagas disease is attained by conventional serological tests such as indirect immunofluorescence, indirect hemagglutination, and ELISA. However, to perform these tests, raw or semi-purified extracts of epimastigote form are used as antigen, and this evolutionary stage of the parasite is only found in the insect vector and not in the vertebrate host. In addition, diagnostic for Chagas disease in the chronic phase may be inconsistent owing to the possible cross-reactions with sera from patients affected by other endemic diseases such as leishmaniasis. In attempt to improve the diagnosis of Chagas disease, a number of recombinant proteins, is now the focus of several studies once they have shown enhancement regarding the sensitivity and specificity. In this work, our group selected four proteins: Tc10, Tc30, Tc80 and Tc170 possibly conserved among different strains of this parasite, which are not present in the predicted proteome of Leishmania species, and that have a high epitope prediction score for B cell by BepiPred program. Among the four selected proteins, the protein termed Tc170 was recombinantly expressed in BL-21 Star bacteria and then used for ELISA experiments against sera from chronic chagasic patients. Sera from patients with visceral leishmaniasis and from healthy individuals were used as control. Thus, ELISA carried out with the pooled sera from patients infected with Leishmania infantum showed higher reactivity with Tc170 protein. This suggests that despite the selected proteins are not present in the proteome of Leishmania species, orthologous peptides between the two forms are present in this protein. We also tested the reaction of the protein Tc170 with individual sera of patients as well with the controls.The results showed that the protein Tc170 had a sensitivity of 84.21% and a specificity of 80% in pool of sera from Chagas patients compared with controls. However, based in our results with distinct test serum, this protein is not suggested for the diagnosis of Chagas disease by presenting a sensitivity of only 25,64% and a specificity of 94,73% among patients with Chagas disease and visceral leishmaniasis. Therefore, search for new targets should be performed in an attempt to obtain a protein with higher sensitivity and specificity, differentiating the T cruzi from other pathogens of the same family.